Uso do resíduo cerâmico procedente de louças sanitárias em substituição parcial ao agregado graúdo em concreto - Nascimento, Gustavo Lira do (2024)
Annually, large amounts of sanitary ware waste (ceramic scrap) are generated due to the disposal of pieces with aesthetic defects. This improper disposal has motivated studies over recent decades investigating the feasibility of reusing these materials, particularly for use in concrete, given that their components are extracted from nature and generate environmental impacts. Therefore, this research aimed to use ceramic scrap from a company located in Caruaru/PE as coarse aggregate in concrete composition. The scrap was crushed to obtain the same granulometry as gravel 1 and replaced it in proportions of 0%, 10%, and 20%. Additionally, to mitigate the effects of the ceramic glaze on some surfaces of the scrap, which hinders the interaction between other concrete components and the scrap, part of this material underwent a preliminary treatment with LP anti-slip, which creates micro-suction cups on ceramic surfaces, aiming to increase the friction coefficient. Thus, five types of concrete were formulated: the reference concrete (CR) without added scrap, concretes with 10% scrap (CS10) and 20% scrap (CS20) without treatment, and concretes with 10% scrap (CT10) and 20% scrap (CT20) with treatment. The research used methodological processes starting with the collection and preparation of the scrap, followed by granulometry and density analysis, composition preparation, test specimen molding, water tank immersion, physical analysis of the test specimens, concrete slump test, and compressive strength testing. In the end, the concretes were classified based on strength and slump values, and concrete porosity was also calculated. The research concluded that the scrap used can serve as a substitute for gravel, considering that in terms of workability, there were no negative effects, as all five types of concrete fell into the S10 slump class. Regarding compressive strength, except for CT20, all concretes fell into the C20 class, achieving the initial goal; additionally, the best concrete was CT10, presenting an average FCK of 22.07 MPa, while the second highest value was the CR, which obtained 21.69 MPa. However, the concrete with the lowest average FCK was CT20, indicating that the use of scrap depends on studies and applications that consider the characteristics of the local materials used.